IMPLEMENTASI SIM800L PADA AKUISISI DATA KWH METER SISTEM IMPULSE DENGAN SENSOR CAHAYA BERBASIS IOT UNTUK MONITORING BIAYA PEMAKAIAN LISTRIK - Sulasmoro, Arfan Haqiqi; Huda, Miftakhul (Politeknik Harapan Bersama Tegal, 2024)
This research is a development of previous research, namely the acquisition of kWh meter data impulse system on household electrical energy consumption with Internet of Thing (IoT)-based light sensors, where for home locations that have not been reached by internet providers this certainly has obstacles. So it is proposed to access it using SIM800L. The methodology used with the stages of designing and making, testing, data analysis, evaluation of research results and preparation of research reports. The system is made by utilizing a light sensor (LDR Sensor) to read the light emitted by the LED impulse kWh meter in this case as much as 3200imp / kWh, the number of impulses received by the LDR sensor is then calculated by the microcontroller and then sent to the cloud. The system is expected to display electricity consumption data directly / real time to the internet through SIM800L module.